Patient-specific effects of soluble factors from Staphylococcus aureus and Staphylococcus epidermidis biofilms on osteogenic differentiation of primary human osteoblasts - Jutta Tübel (Nature Portfolio, 2021)
Abstract Due to the frequency of biofilm-forming Staphylococcus aureus and Staphylococcus epidermidis in orthopedics, it is crucial to understand the interaction between the soluble factors produced by prokaryotes and their effects on eukaryotes. Our knowledge concerning the effect of soluble biofilm factors (SBF) and their virulence potential on osteogenic differentiation is limited to few studies, particularly when there is no direct contact between prokaryotic and eukaryotic cells. SBF were produced by incubating biofilm from S. aureus and S. epidermidis in osteogenic media. Osteoblasts of seven donors were included in this study. Our results demonstrate that the detrimental effects of these pathogens do not require direct contact between prokaryotic and eukaryotic cells. SBF produced by S. aureus and S. epidermidis affect the metabolic activity of osteoblasts. However, the effect of SBF derived from S. aureus seems to be more pronounced compared to that of S. epidermidis. The influence of SBF of S. aureus and S. epidermidis on gene expression of COL1A1, ALPL, BGLAP, SPP1, RUNX2 is bacteria-, patient-, concentration-, and incubation time dependent. Mineralization was monitored by staining the calcium and phosphate deposition and revealed that the SBF of S. epidermidis markedly inhibits calcium deposition; however, S. aureus shows a less inhibitory effect. Therefore, these new findings support the hypotheses that soluble biofilm factors affect the osteogenic processes substantially, particularly when there is no direct interaction between bacteria and osteoblast.